Nail society of india recommendations for treatment of onychomycosis in special population groups - Khushbu Mahajan; Chander Grover; Vineet Relhan; Sushil Tahiliani; Archana Singal; Manjunath M Shenoy; Deepak Jakhar; Shikha Bansal (Wolters Kluwer Medknow Publications, 2024)
Onychomycosis (OM) is a difficult-to-treat condition, especially considering the limited armamentarium of antifungal drugs, need for prolonged treatment, and poor compliance. This problem is further confounded while treating OM in special populations such as children, elderly, immunosuppressed patients, pregnant or lactating women, and patients with chronic liver or kidney disease. In the absence of standardized treatment guidelines, the antifungal therapy is either withheld or compromised, as it is largely governed by personal preferences or based on anecdotal reports. Hence, an expert group of the Nail Society of India worked towards drafting guidelines based on established literature and inputs from experts, with practical recommendations for the treatment of onychomycosis in special population groups. An extensive analysis of available English language literature on onychomycosis in special populations, published during a 10-year period (2014-2023 until date) was done. The available studies and reports were evaluated, cross-references read, and evidence compiled, graded, and discussed by the expert group to derive consensus recommendations for practice. The evidence and recommendations based on it are presented in a narrative format to guide treatment choices when dealing with population groups with special considerations.